Investigation on the effects of electrical transients on power system using electromagnetic transient program - Azhar Khairuddin, 1963-; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Elektrik; Universiti Teknologi Malaysia. Pusat Pengurusan Penyelidikan (Skudai : Universiti Teknologi Malaysia, 2006)
PSZJBL